(untitled) (Journal of Health Sciences, 2019)
Anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) is rare, but life-threatening condition. The treatment of choice in patients with ALCAPA is the establishment of a dual coronary artery system with surgical reimplantation of the left coronary artery in the left coronary sinus. Percutaneous coronary intervention is infrequent in the pediatric population but can be a life-saving by promptly restoring flow to an obstructed coronary artery. It is a highly demanding and high-risk procedure in infants due to the technical difficulties and the small coronary artery diameter in infants.